2017
DOI: 10.1590/s0102-865020170030000005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic saline solution associated to remote ischemic perconditioning in kidney ischemia/reperfusion injury in rats

Abstract: Remote ischemic perconditioning associated or not to saline solution promoted reduction of acute renal injury induced by ischemia/reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, hypertonic saline, which has protective effects on ischemia reperfusion, as well as antioxidant and anti-apoptotic effects [29,30], protect kidneys from injury. Furthermore, Kreimier et al showed that hypertonic saline solution effectively improved renal microcirculation [31] and protected shock kidney by infusion of small doses [32]. This study basically supports this theory.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, hypertonic saline, which has protective effects on ischemia reperfusion, as well as antioxidant and anti-apoptotic effects [29,30], protect kidneys from injury. Furthermore, Kreimier et al showed that hypertonic saline solution effectively improved renal microcirculation [31] and protected shock kidney by infusion of small doses [32]. This study basically supports this theory.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, in the samples of intestinal tissue, there was a difference between sham and perconditioning groups when compared to the IR, suggesting that the ischemic-reperfusion process to which the animals in the IR group were submitted resulted in an increase in the levels of free radicals, as well as, consequently, in the involvement of oxidative stress 23 .…”
Section: Discussionmentioning
confidence: 95%
“…RIPerC, as one of the effective and newest protective techniques, alleviates renal (Brito et al 2017;Ogawa et al 2001;Sedaghat et al 2016) and liver IRI (Costa et al 2014) Under stress conditions such as renal I/R, after prolonged ischemia, blood flow reperfusion leads to production of reactive oxygen species (ROS) from damaged mitochondria (Granger and Kvietys 2015). An unbalance between ROS production and defensive capacity of the cells leads to oxidative stress (Birben et al 2012;Tarantino et al 2011).…”
Section: Discussionmentioning
confidence: 99%